Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.5897/jco2019.0199
|View full text |Cite
|
Sign up to set email alerts
|

Technological application of the butter of Pentadesma butyracea: A comparative evaluation of its cosmetic behaviour with Vitellaria paradoxa butter

Abstract: Pentadesma butyracea butter is a vegetable fat obtained from the kernels of the P. butyracea tree. It is a potential source of fat for the food and cosmetics sectors. This study evaluated the quality characteristics of the cream and soap processed from the butter of P. butyracea in comparison to similar product from the Vitellaria paradoxa butter. The same cosmetic products were produced with P. butyracea and V. paradoxa butters. The two types of butter are extracted using the traditional procedure. The qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
(28 reference statements)
0
5
1
Order By: Relevance
“…Moreover, the values for FWO and FSO samples were similar to those of the commercial CBM. The USM values we recorded for PBSB samples are higher than those (1.55% to 1.8%) reported by [ 2 , 33 ] and [ 3 ]. Shea butter is reported to have a higher USM, between 4 and 11% [ 28 ].…”
Section: Resultscontrasting
confidence: 85%
See 3 more Smart Citations
“…Moreover, the values for FWO and FSO samples were similar to those of the commercial CBM. The USM values we recorded for PBSB samples are higher than those (1.55% to 1.8%) reported by [ 2 , 33 ] and [ 3 ]. Shea butter is reported to have a higher USM, between 4 and 11% [ 28 ].…”
Section: Resultscontrasting
confidence: 85%
“…Lower PVs of 0.74 meqO2/kg and 2.09 meqO 2 /kg have been reported for P. butyracea butter and shea butter, respectively [ 5 ]. In another study, [ 33 ] reported 2.17 meqO2/kg and 3.78 meqO2/kg for P. butyracea butter and shea butter, respectively. Tchobo et al [ 2 ] noted a higher PV of 17.30 meqO2/kg for P. butyracea butter.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Aissi et al (2011), the PV of Pentadesma butter varies with pretreatment operations of kernels and butter, ranging from 0.83 to 1 meq O 2 kg −1 . Ayegnon et al (2019) recently reported a PV of 2.7 meq O 2 kg −1 for Pentadesma butter. These values were lower than those of shea butter (0.5-29.5 meq O 2 kg −1 ) reported by several researchers (Dandjouma et al, 2009;Honfo et al, 2014) and also were lower than the maximum value of 10 meq O 2 kg −1 required for cosmetic uses (Iddrisu et al, 2019;NBF 01-005, 2006).…”
Section: Qualit Y Char Ac Teris Tic S Of Pentade Sma But Termentioning
confidence: 98%